The Challenges of Unique Poverty Alleviation Policies in Banten and Yogyakarta - Jati, Wasisto Raharjo (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2025)
Poverty remains a persistent challenge nationally and subnationally. Reliance on ineffective grants fuels poverty. This study analyzes innovative poverty alleviation policies in Banten and Yogyakarta, focusing on inter-branch interactions. Collaboration is key to creating better joint policies and maintaining parliamentary oversight of the government’s programs. The purpose of this study is to outline the challenges and factors that influence the success of innovative policies in both regions. This study uses a qualitative approach and a comparative case study design. Data were collected through in-depth interviews, in-depth fieldwork, focus group discussions (FGDs), and document analysis conducted between 2015 and 2017, and analyzed using a deductive thematic approach. The results of this study show that poverty alleviation approaches should be tailored based on thematic analysis of each region. This study suggests a best practice approach to evaluate policy effectiveness. Therefore, this study recommends that the DPR RI collaborate with the government for optimal policy implementation. In addition, the DPR RI needs to promote poverty-related legislation, conduct cross-sectoral and cross-actor oversight, and/or reform the poverty budget mechanism.